Solar Photolysis and Photocatalytic Decolorization of Thymol Blue - Falah H. Hussein; Ahmed N. Alkhateeb; Jameel K. Ismail (E-Journal of Chemistry)
The photolysis and photocatalytic decolorization of an aqueous propane-2-ol solution of thymol blue(TB) (Phenol, 4,4'-(3H-2,1-benzoxathiol-3-ylidene)bis(5-methyl-2-(1-methylethyl)-,S,S-dioxide; Thymolsulfonpthalein) (C27H30O5S),were carried out under natural weathering conditions. Direct photolysis of TB solution of concentration 4.3X10−3 M degraded 37.1% of the colored solution after two hours of solar irradiation, however, the solar photocatalytic decolorization percentage reached 79.04% and 86.21% after the addition of zinc oxide and titanium dioxide, respectively, for the same period. The degradation percentages were investigated by monitoring the dye decolorization spectrophotometrically. The decolorization rates of TB are markedly related with amount of hydroxyl radical formed. A suitable mechanism for the mineralization of TB has been proposed.